2021
DOI: 10.3390/ijerph18136894
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Nutritional Status of Syrian Refugee Mothers and Their Children under Five Years in Greater Beirut, Lebanon

Abstract: The objective was to assess the prevalence of anemia and nutritional status of mothers and children under five years among Syrian refugees in Lebanon and to identify nutritional deficiencies among pregnant, lactating, and non-pregnant non-lactating (NPNLM) mothers. A cross-sectional study was conducted among Syrian refugee mothers with children under five years in Greater Beirut, Lebanon (n = 433). Data on socio-economic status, maternal health, lifestyle characteristics, dietary intake, anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 74 publications
5
39
0
Order By: Relevance
“…The anemia level in our study were not too far from findings recorded in Argentina (28.9%) [57] and South Africa (33%) [58]. As for wasting, recent surveys conducted among Syrian refugees and Lebanese children aged six to 59 months in Lebanon showed that childhood wasting was maintained to about 5% in 2018-2021 [17,50]. However, a similar prevalence of wasting was found among infants of Sahrawi refugees [47].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The anemia level in our study were not too far from findings recorded in Argentina (28.9%) [57] and South Africa (33%) [58]. As for wasting, recent surveys conducted among Syrian refugees and Lebanese children aged six to 59 months in Lebanon showed that childhood wasting was maintained to about 5% in 2018-2021 [17,50]. However, a similar prevalence of wasting was found among infants of Sahrawi refugees [47].…”
Section: Discussionsupporting
confidence: 54%
“…In addition, Syrian refugees in Turkey reported that malnutrition and fatigue of mothers were often the biggest obstacles to breastfeeding [59]. These findings shed the light on the role of adequate maternal nutrition during pregnancy and lactation as it impacts the development and health of the offspring [75,76], which was particularly difficult to achieve among Syrian refugee mothers in Greater Beirut, Lebanon [17,18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous reports also showed that Syrian refugees are at risk for inadequate antenatal care, adolescent pregnancy, and adverse pregnancy outcomes [ 47 , 48 ]. In addition, nutritional inadequacy was identified in higher proportions of lactating and pregnant Syrian refugee mothers in Turkey and Lebanon [ 48 , 49 ]. Promoting the education of girls will greatly contribute to the healthy nutrition of Syrian children by both increasing health literacy and preventing adolescent marriages.…”
Section: Discussionmentioning
confidence: 99%
“…In across sectional study among Syrian refugees anemia prevalence based on hemoglobin concentration was estimated to be 48.4% in Zaatari camp under ve years old children in Jordan (49,50), and 25.8% anemia prevalence in Lebanon (50). In most recent assessment anemia recorded 30.5% prevalence under ve years old children in Greater Beirut in Lebanon (51).…”
Section: Child Health Assessmentmentioning
confidence: 97%